Extensive reading to improve students’ writing of explanation text - Siti Nur Aida; Elok Widiyati (EduLite: Journal of English Education, Literature and Culture, 2020)
This research aims at finding out whether or not the use of extensive reading is effective for teaching writing explanation text to the eleventh grade at Islamic University in Semarang. Quasi experimental research was applied as the method. The researchers took two groups as the sample, they were XI MIPA 6 as the experimental class and XI MIPA 2 as the control class. The total subject of this research was 65. This research used SPSS in analysing the data of writing test through several activities. They were pre-test before treatments, and post-test after treatments. The result of the research shows the significance difference in the writing ability of explanation text between eleventh-graders who were taught by using extensive reading and those were not taught by using it. It can be seen in the result of mean score in the post-test of experimental class which is 64.4118 and control class which is 48.5484 and as a result Sig. (2-tailed) is 0.00 < 0.05. Therefore, the null hyothesis of this research is rejected. It means that the use of extensive reading had significantly improved the eleventh-graders’ writing ability of the explanation text in English teaching and learning process of the experimental class at Islamic School in Semarang in the academic year 2018/2019.